Long-term effects of environmental policies on educational performance: Evidence from China - Siwar Khelifa; Jie He (University of Neuchâtel, Institute of Economic Research (IRENE), 2023)
This paper examines the overall long-term effects of the Two Control Zones policy, implemented by the Chinese government to reduce air pollution, on children's human capital development. Estimates show that exposure to this policy, during the year of birth, is associated, 15 years later, with an increased probability to obtain better standardized test scores and thus to join a higher quality high school and an increased probability to join an academic high school. These results provide an additional evidence in favor of environmental policies as promising inputs for human capital formation. The beneficial effects are found to be accentuated among girls and children born to fathers with low education levels, suggesting that environmental regulations may help reducing some of the educational disparities, in a developing country context. Projecting forward, results also suggest better future higher education and labor market outcomes. The findings are robust to various alternative hypotheses and specifications.
Keywords: I18; I24; J24; Q51; Q56; 330; Education; environmental policy; early-life conditions; China